2016
DOI: 10.3109/14767058.2016.1163683
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of the skin-to-skin cesarean section – a retrospective cohort study

Abstract: Adverse maternal and neonatal outcomes were not increased after skin-to-skin cesarean compared to conventional cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 15 publications
0
28
0
6
Order By: Relevance
“…Patient satisfaction of clinical services in pre-, peri-, and postoperative periods is a multidimensional subjective concept (6). Based on reports from the United Kingdom, 75% of CS deliveries were performed under general anesthesia 25 years ago, which has decreased to 16% today (7).…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction of clinical services in pre-, peri-, and postoperative periods is a multidimensional subjective concept (6). Based on reports from the United Kingdom, 75% of CS deliveries were performed under general anesthesia 25 years ago, which has decreased to 16% today (7).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have, however, demonstrated the safety of skin-to-skin contact at the time of cesarean section: the procedure does not seem to increase the risk of neonatal hypothermia [19], maternal surgical infections, or maternal bleeding [20]. However, the duration of the surgery was prolonged by 4 min in a group of women having skin-to-skin contact during cesarean section compared to women not having early skin-to-skin contact [20].…”
Section: Parental Experiences Around C-sectionmentioning
confidence: 94%
“…Family-centered cesarean birth, or skin-to-skin cesarean birth, is a new option that involves immediate skin-to-skin contact between the newborn and mother in surgery. However, this new cesarean protocol has not been widely adopted in hospitals due to safety concerns around the mother’s ability to hold her newborn while on an operating room table and concerns related to postpartum hemorrhage and infection (Posthuma et al, 2016). In a recent study comparing conventional cesarean birth to skin-to-skin cesarean birth, investigators did not see increases in either of these adverse outcomes, but did find that skin-to-skin treatment was associated with a decrease in both neonatal admission to the neonatal nursery and neonatal work-ups for infection (Posthuma et al, 2016).…”
Section: Implications Of Route Of Birthmentioning
confidence: 99%